2023
DOI: 10.1007/s12397-023-09477-y
|View full text |Cite|
|
Sign up to set email alerts
|

Tongue Ties or Fragments Transformed: Making Sense of Similarities and Differences between the Five Largest English-Speaking Jewish Communities

Abstract: The subjects of Jewish identity and Jewish communal vitality, and how they may be conceptualized and measured, are the topics of lively debate among scholars of contemporary Jewry (DellaPergola 2015, 2020; Kosmin 2022; Pew Research Center 2021; Phillips 2022). Complicating matters, there appears to be a disconnect between the broadly accepted claim that comparative analysis yields richer understanding of Jewish communities (Cooperman 2016; Weinfeld 2020) and the reality that the preponderance of that research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…These large sample sizes enable examinations of the upbringing of Jews of a wide range of backgrounds. Comparative research has revealed some similarities but also notable differences between Australian Jews and those from other English-speaking Jewish communities (Bankier-Karp 2023a). This suggests it is important to conduct research focusing on young Australian Jews, to better understand the salience of Jewish cultural engagement and examine its effects on identity formation, so change over time can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…These large sample sizes enable examinations of the upbringing of Jews of a wide range of backgrounds. Comparative research has revealed some similarities but also notable differences between Australian Jews and those from other English-speaking Jewish communities (Bankier-Karp 2023a). This suggests it is important to conduct research focusing on young Australian Jews, to better understand the salience of Jewish cultural engagement and examine its effects on identity formation, so change over time can be determined.…”
Section: Introductionmentioning
confidence: 99%